PELAKSANAAN PENDIDIKAN ASWAJA UNTUK MENANGKAL PAHAM RADIKALISME DI UNIVERSITAS KH. A. WAHAB HASBULLAH JOMBANG - Ali - Mutaqqin (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2020)
Since its inception, Islam which has been growing and developing in Nusantara is Islam Ahlussunnah wal Jama'ah (Aswaja). Islam Aswaja which is believed and practiced by Muslims in Nusantara is taught from generation to generation. The establishment of Jam'iyyah Nahdlatul Ulama (NU) is the institutionalization of Islam Aswaja as an effort to protect and teach it to the Muslims in Nusantara from time to time. Islam Aswaja combines three dimensions at once in Islam, namely aqidah, fiqh and Sufism, and principled on the values ​​of tawassuth (moderate), tawazun (balanced), tasammuh (tolerant) and ta'dil (fair). People who believe in and practice Aswaja will have moderate, tolerant and upright views and actions in social life. This paper analyzed the implementation of Aswaja education at KH University. A. Wahab Hasbullah Jombang (Unwaha), a tertiary educational institution affiliated with Jami‘iyah Nahdlatul Ulama. The problem discussed is how Aswaja's education in Unwaha. The results of this study are: First, Aswaja education aims to provide understanding and belief of Aswaja Islam to students, and counteract the understanding of extremism, radicalism and religious liberalism. Second, Aswaja education in Unwaha is carried out with two approaches, namely the learning approach in the form of lectures on Aswaja Thought courses for one semester that must be followed by students of all study programs, and the habituation approach of Aswaja al-Nahdliyah in daily life in the campus environment